1999
DOI: 10.1001/archinte.159.18.2213
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to Writing Do-Not-Resuscitate Orders

Abstract: Limitations in the extent and depth of the physician-patient relationship appear to be the most frequent impediments to writing DNR orders in our institution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 37 publications
0
19
0
1
Order By: Relevance
“…The frequency of DNACPR orders established within the 72 h after admission was 53%, which is higher than the data previously documented in the scientific literature (8.6-24% and even 40% in a nursing home) [6][7][8][12][13][14][15]. Only 39% of these decisions involved the patients and/or their relatives.…”
Section: Prevalence Of the Dnacprmentioning
confidence: 79%
See 2 more Smart Citations
“…The frequency of DNACPR orders established within the 72 h after admission was 53%, which is higher than the data previously documented in the scientific literature (8.6-24% and even 40% in a nursing home) [6][7][8][12][13][14][15]. Only 39% of these decisions involved the patients and/or their relatives.…”
Section: Prevalence Of the Dnacprmentioning
confidence: 79%
“…Numerous publications exist about the difficulties encountered by a medical team faced with the DNACPR order [7,8]. In Switzerland, the first directives were published in 2008 and reviewed in 2013 to conform with changes in Swiss legislation, where more autonomy is given to the patient's legal representative, when the patient is unable to make a decision [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A DNR order is unique because unlike other orders, CPR is done without an explicit doctor's order 34 or the patient's consent. 1-3,7,8,14-17, [24][25][26][27][28]35 According to the 1994 ACLS textbook, 1 DNR means: "In the event of an acute cardiac arrest, no CPR measures will be instituted or continued." It was suggested that the terms "Do Not Attempt Resuscitation" (DNAR) or "No CPR" are more appropriate because the term "do-not-resuscitate" suggests that a person could be resuscitated if CPR were performed.…”
Section: Dnr Ordersmentioning
confidence: 99%
“…Despite this, the presumption of resuscitation and the practice of attempting CPR on all hospitalized patients regardless of the underlying disease process persists unless there is consent from the patient or surrogate decision maker for a do-not-resuscitate (DNR) order. 1,2,4,[6][7][8][9][10][11][12][13][14][15][16][17]21,22,[24][25][26][27][28] The choice for attempting CPR is inherently a consideration in all hospitalized patients whether or not the issue is addressed. If it is not addressed, a resuscitation effort will automatically occur by default if a patient has a cardiopulmonary arrest.…”
mentioning
confidence: 99%